Cutaneous manifestations of COVID-19 in patients hospitalized in a university hospital in Rio de Janeiro: descriptive study (Research, Society and Development, 2023)
Introduction: The coronavirus is an infectious disease, which in its classic presentation causes a viral infection followed by pulmonary and systemic inflammation, being observed in some patients in addition to respiratory symptoms, cutaneous manifestations. The severity and complexity of the patients also determined inevitable pressure injuries (PL), being relevant differential diagnosis of injuries secondary to COVID-19, especially livedoid and purpuric. Objective: to identify the cutaneous manifestations found in the medical records of patients with COVID-19; describe the profile of patients affected by cutaneous manifestations related to COVID-19; to determine the incidence rate of these skin lesions in the analyzed population and to describe the main preventive care for the prevention of skin lesions. Method: documentary, retrospective, quantitative study, which took place between September 2021 and November 2022 at a university hospital in Rio de Janeiro. Results: 596 patients analyzed, 98 of them with 155 diagnosed skin lesions: 15 secondary to COVID-19 - 09 (5.80%) livedoid, 03 (1.93%) cyanosis and 03 (1.93%) purpuric lesions , in addition to 111 (71.61%) LP and 29 (18.70%) mixed lesions. PI had an incidence of 18.62%, followed by mixed injuries, with a rate of 4.86%, and injuries secondary to COVID-19, with 2.51%. Conclusion: COVID-19-related injuries were less frequent than PI, confirming the inevitability referred to by the NPIAP. Therefore, more epidemiological studies are needed. Regarding skin care, basic measures to maintain its integrity must respect good hygiene and hydration practices.